Pemberdayaan Sumber Daya Desa Sukawijaya melalui Teknologi Informasi - Purnomo, Rakhmat; Putra, Tri Dharma (Jurnal Sains Teknologi dalam Pemberdayaan Masyarakat, 2020)
Community Service Program in Real Work Lectures or PKM-KKN aims to train student soft skills. A companion lecturer is determined to guide and direct 30 students. The PKM-KKN program is carried out in Desa Sukawijaya, Kecamatan Tembelang, Kabupaten Bekasi, West Java. Our main program is technopreneur socialization and internet marketing. The implementation method is by sharing knowledge and experience through socialization activities to youth youths and students of the Aliyah Al-Hidayah Madrasah School in Desa Sukawijaya. The results of PKM-KKN activity are youth youths and students of the Aliyah Al-Hidayah Madrasah school in Desa Sukawijaya are expected to behave wisely in the use of information technology devices, especially smartphones and the internet to optimize the potential of personal competence, personal effort and the potential of Sukawijaya Village community.